Lotte per la dignità - Di Iasio, Domenico (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2022)
The West, that always appear as show, appearance, and publicity, strive to comprehend the class struggle which, observes Marx, had not been invented by him, but he only discovered it in the tangible reality of history. Often, the class struggle simply materialises itself in war. Paradoxically, a tycoon, Warren Buffet, comments on it today, however putting emphasis on the fact that the class struggle or war is currently won by the class which he belongs, the upper class, and the rich grow richer and richer against the poor who become poorer and poorer. Inequality of social classes and nations is the main problem of our historical time period. Dignity restoration is necessary, to those who need it, the poor and the less developed countries in the world. It is fundamental to build a sustainable equality. Struggle for Recognition; Freedom; Equality.